Concentrated solar power systems - Pragathi, Bellamkonda; Kothari, D. P. 1944- (Wiley, 2025)
Follow the performance assessment tools and methods currently used for concentrated solar power technology (CSP) in this unique, single source overview The search for renewable energy sources and methods for harnessing them is perhaps the most significant challenge of the twenty first century, which faces the potentially existential crises of global climate change. Concentrated solar power, or CSP, has the potential to revolutionize energy production. Its integration of thermal energy and its capacity to work with traditional power generation cycles make it an ideal tool for a newly sustainable world. Concentrated Solar Power Systems is an advanced-level book offering both theoretical and practical perspectives on CSP. Its thorough overview of this technology includes the foundational scientific principles, system design and development, and growing applications. It offers a one-stop source for the performance assessment tools and methods currently deployed in the area of concentrated solar power. Readers will also find: - Case studies throughout showing CSP harnessed to meet real energy needs- Detailed discussion of topics including site selection, feasibility analysis, environmental assessments, and more- Analysis of specific technologies including linear Fresnel reflectors, parabolic troughs, concentrating photovoltaic systems, and many othersConcentrated Solar Power Systems is ideal for students and researchers involved or interested in the design, production, development, optimization, and application of CSP technology